Depresión postparto y su incidencia en la conducta de una mujer de 29 años de edad de la ciudad de Colimes de la Provincia del Guayas - Soriano Silva, Isabel Aracelly (2022)
The following investigation aims to analyze how postpartum depression affects the behavior of a 29-year-old woman. Faced with the established problem, some techniques and instruments have been used such as: clinical observation, clinical history, semi-structured interview, Edithburn's Postpartum Scale Test, Beck's Depression Test, whose function is to assist professionals in the area to achieve a certain and assertive diagnosis. It should be noted that there are different factors that influence the emotional state of the patient. It is also known that women enter a special state during the first weeks of childbirth where there is a probability of developing this disorder due to different hormonal changes. It should be noted that postpartum depression disorder should be treated with psychological and family support and in the event of any change in behavior that affects the patient in different personal areas, seek specialized help, since with due attention the patient can return to life normal.